Pengaruh Struktur Modal, Keputusan Investasi Dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada Sub Sektor Pertambangan Batubara Yang Terdaftar Di BEI - Ella Sofiatun Nisah; Joni Hendra; Elok Dwi Vidiyastutik (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research was conducted on companies in the coal mining subsector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022 with the aim of determining the influence of Capital Structure, Investment Decisions, and Dividend Policy both partially and simultaneously on Firm Value in the coal mining subsector companies listed on the Indonesia Stock Exchange (IDX).The type of research used is quantitative, with an associative approach, involving variables such as Capital Structure, Investment Decisions, and Dividend Policy. The sample used in this study consists of 14 companies with 3 years of observation. The data analysis technique employed is multiple linear regression using SPSS 25. The research results indicate that the Capital Structure variable does not have a significant effect on firm value, while Investment Decisions and Dividend Policy have a significant effect on firm value. Simultaneously, the variables of Capital Structure, Investment Decisions, and Dividend Policy significantly influence firm value. Among the three variables, Investment Decisions have the most dominant effect on firm value, as indicated by the Standardized Coefficients Beta value of 0.640, with a t-value (4.871) higher than the others.